What Drives Preventive Health Behavior During a Global Pandemic? Emotion and Worry. Issue 8 (24th June 2021) - Coifman, Karin G; Disabato, David J; Aurora, Pallavi; Seah, T H Stanley; Mitchell, Benjamin; Simonovic, Nicolle; Foust, Jeremy L; Sidney, Pooja Gupta; Thompson, Clarissa A; Taber, Jennifer M
Abstract: Background & Purpose: Primary prevention of COVID-19 has focused on encouraging compliance with specific behaviors that restrict contagion. This investigation sought to characterize engagement in these behaviors in U.S. adults early during the pandemic and to build explanatory models of the psychological processes that drive them. Methods: US adults were recruited through Qualtrics Research Panels ( N = 324; 55% female; M age = 50.91, SD = 15.98) and completed 10 days of online reports of emotion, COVID-19 perceived susceptibility and worry, and recommended behaviors (social distancing, hand washing, etc.). Factor analysis revealed behaviors loaded on two factors suggesting distinct motivational orientations: approach and avoidance. Results: Changes in approach and avoidance behaviors over the 10 days indicated large individual differences consistent with three types of participants. Discrete emotions, including fear, guilt/shame, and happiness were associated with more recommended behaviors. Fear and COVID-19 worry indirectly influenced each other to facilitate more behavioral engagement. While emotions and worry strongly predicted individual differences in behavior across the 10 days, they did not predict as well why behaviors occurred on one day versus another. Conclusions: These findings suggest how daily affective processes motivate behavior, improving the understanding of compliance and efforts to target behaviors as primary prevention of disease. Abstract : Daily diaries revealed U.S. adults exhibit diverse patterns of engagement in COVID-19 preventive behaviors. Emotions and COVID-19-related worrybut not estimates of perceived disease riskdrive recommended behaviors.